The Correlation between The Intensity of Parent – Child Communication, Peer Groups, and Girl’s Interest to Marry Early - Merina Wulandari; Dra. Sri Widowati Herieningsih, MS (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The background of this research is based on many cases of early mariages that under age girls do. Early marriages that occur in children is related with their sorroundings, such as family and peer groups. This research aims to determine the correlation of the intensity of parent – child communication, the intensity of communication with peer groups, an girl’s interest to marry early. The method which is used in this research is the quantitative with positivistic approach. This research used The Reasoned Action Theory and The Reference Group Theory. This research is using non probability samling technique. The population in this research is girls age 10-16 in Indramayu district. While the sample is 60 respondens. The data is analyzed with the aid of SPSS aplication with Pearson correlation test. The result of this research indicate there is correlation between the intensity of parent – child communication and girl’s interest to marry early with significance value is 0,001 and Pearson correlation value is -0,434. It means the correlation’s power of the intensity of parent – child communication and girl’s interest to marry early is medium with not unidirectional. So, if the intensity of parent – child communication is high, then girl’s interest to marry early is low. If the intensity of parent – child communication is low, then girl’s interest to marry early is high. And also there is correlation between the intensity of communication with peer groups and girl’s interest to marry early with significance value is 0,006 and Pearson correlation value is 0,353. It means the correlation’s power is weak and unidirectional. So, if the intensity of communication with peer groups is high, then girl’s interest to marry early is high. If the intensity of communication with peer groups is low, then girl’s interest to marry early is low. The suggestion of the researcher is for the goverment to give counseling for parents through BKKBN about early marriage and its impact, and also for parents go intensify the communication with their children, so the children will get knowledge and a good understanding about early marriage and its impact on them. The counseling can be done through local resident’s regular meeting.